2003
DOI: 10.1021/ma020937f
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Polymers in Organosilicate Nanocomposites

Abstract: Dynamic secondary ion mass spectrometry (DSIMS) measurements were performed to measure the effects of functionlized organosilicate clay (Cloisite 6A) on the tracer diffusion coefficient, D, in polystyrene (PS) and poly(methyl methacrylate) (PMMA) matrices. The results indicate that D is unaffected by the addition of 5% (by volume) of PS and is reduced by a factor of 3 with the addition of the same volume fraction in a PMMA matrix. The same ratio was also obtained for the extrapolated zero shear rate viscosity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
1
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 13 publications
3
29
1
1
Order By: Relevance
“…This has several important implications on the interaction of the clay platelets when they are dispersed within a polymer blend. In contrast to expectations, that decreasing the surfactant coverage would allow the clays to disperse in polymers of varying polarity, we found that all clays, except the most polar (10A) were easily dispersed within slightly polar homopolymers, such as EVA and PMMA [22][23][24][25]. On the other hand, when highly immiscible blends were formed between polar and non-polar polymers, Si et al [10] reported that these clays were non-specific compatibilizers of a large class of blends.…”
Section: Resultscontrasting
confidence: 93%
“…This has several important implications on the interaction of the clay platelets when they are dispersed within a polymer blend. In contrast to expectations, that decreasing the surfactant coverage would allow the clays to disperse in polymers of varying polarity, we found that all clays, except the most polar (10A) were easily dispersed within slightly polar homopolymers, such as EVA and PMMA [22][23][24][25]. On the other hand, when highly immiscible blends were formed between polar and non-polar polymers, Si et al [10] reported that these clays were non-specific compatibilizers of a large class of blends.…”
Section: Resultscontrasting
confidence: 93%
“…In addition, the sputter rate is significantly reduced when employing atomic beams, such that only dynamic SIMS instruments are typically used. There are several examples of polymeric depth profiling with atomic beams including PS (Whitlow & Wool, 1989, 1991Zhao et al, 1991;Shwarz et al, 1992;Liu et al, 1995;Zheng et al, 1995;Strzhemechny et al, 1997;Rysz et al, 1999;Yokoyama et al, 1999;Shin et al, 2001;Hu et al, 2003;Lin et al, 2003;Harton, Stevie, & Ade, 2006a,b,c;Harton et al, 2006d), PAMA (Valenty et al, 1984), PBMA (Verhoeven et al, 2004), PEVA (Verhoeven et al, 2004), PC (Valenty et al, 1984), PVDF (Chujo, 1991), PEO (Mattsson et al, 2000;Huang et al, 2001), PMMA (Chujo, 1991;Huang et al, 2001;Hu et al, 2003;Harton, Stevie, & Ade, 2006a,b,c;Harton et al, 2006d), polydimethyl phenylene oxide (PDPO) (Lin et al, 2003), PVP (Zheng et al, 1995;Pinto, Novak, & Nicholas, 1999;Yokoyama et al, 1999;Harton, Stevie, & Ade, 2006a,b;Harton et al, 2006d), PPV and other polymer based LED materials Bulle-Lieuwma & van de Weijer, 2006), solar cell materials (Bulle-Lieuwma et al, 2003), conducting polymers (Gray et al, 1992), video tapes (Chujo, 1991), silicones …”
Section: B Atomic Ion Bombardment Of Polymersmentioning
confidence: 99%
“…Studies with silica nanoparticles 33 found a monotonic decrease in diffusion constant with increasing filler concentration, another study with nanoclays found no change in diffusion coefficient at 5% clay content in polystyrene with a factor of three decrease in polymethyl methacrylate. 34 The results for carbon nanotubes are significantly more complicated. In two studies by Winey et al, 35,36 the authors found a minimum in diffusion constant with nanotube content in the case of single-walled and multiwalled nanotubes.…”
Section: Dynamics: Glass Transition and Diffusion Coefficientmentioning
confidence: 99%